Nurses' napping practices and their effects on sleepiness, fatigue, well-being, and quality of nursing care - Dawa Gyeltshen; Kinley Gyaltshen; Nima Dorji; Kinley Yangdon; Neten Wangchuk; Loday Drakpa (Tehran University of Medical Sciences, 2023)
Background & Aim: Napping is one of the evidence-based countermeasures to fatigue and decreased alertness during night shift work. We aimed to understand night shift nurses' napping practices and study the effectiveness of different nap lengths on sleepiness, fatigue, well-being, and the quality of nursing care. Methods & Materials: A comparative descriptive design was used. Data were self-reported by 305 nurses using the Questionnaire on Night Shift Napping Practices, the Karolinska Sleepiness Scale, the Fatigue Visual Analog Scale, the Everyday Feeling Questionnaire, and the Quality of Nursing Care Questionnaire. Data collection was done over 4 months between August and November 2022. Frequency tables, Mean, and standard deviation were used to describe data, and One-way analysis of variance (ANOVA) was used for means comparisons. Results: About 40% of the nurses reported that they took naps during their night shifts. The majority (82.92%) reported that they napped for more than 45 minutes (N= 305). Napping was found to significantly reduce sleepiness (P= 0.002) and fatigue (P= 0.001), and improve the quality of nursing care (P= 0.03). The group who napped for more than 45 minutes reported significantly reduced levels of sleepiness (P= 0.02) and fatigue (P= 0.01) when compared to the group who either didn't nap or napped for less than 45 minutes. Conclusion: This study suggests that implementing nap interventions for nurses on night shift can be an effective method to reduce sleepiness and fatigue, and improve patient care.